Pengaruh Perilaku Konsumen terhadap Keputusan Pembelian Tiket Pesawat Secara Online pada Situs Tiket.Com Periode 2021 - Anisa Ul Aliah; Nanik Riananditasari (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Transactions in shopping are things that cannot be separated from the community in order to carry out life. Judging from the transaction process carried out in the era before digitization, it required consumers to come to see the seller in order to get the goods or services they needed and wanted. With digitalization happening on a large scale in the community, it can facilitate the transaction process for consumers. There are many factors that can have an impact as a result of this extraordinary change, these factors include cognitive, cultural, social and personality factors of a person. This study is intended to find out changes in attitudes in individuals due to online flight ticket transactions on the tiket.com website. The quantitative approach acts as the method used in this study with the support of a simple regression analysis step. The sample used in this study was 100 samples. The conclusion of this study shows that the number of individual attitudes has a relevant impact on the choice to make transactions to buy airline tickets online on the tiket.com website. Thus it can be proven from the value in a simple linear regression analysis worth, Y = 2.762 + 0.306X. This value shows that consumer attitudes have a good impact on the choice to buy, which is worth 59%.